Islamic Banking Methods When Facing Increased Gold Pawn Production at Sharia Bank KC Kabanjahe - Nurianti Rahmadani; Ahmad Amin Dalimunthe (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The implementation of gold pawning is part of Islamic financial institutions in 2011-2012, the level of pawning is very large but can help supply customers. This research aims to find out how Islamic banking is when dealing with developers of gold pawning production. In the face of increased production of gold pawnshops, the problem that occurs is the production of gold pawnshops, and the assumption given by the Islamic bank KC Kabanajahe to overcome these problems. The method used in this research is a qualitative method using primary data in the form of documents and slides related to gold pawn financing, while for secondary data in the form of information from the internet, books, journals, theses, articles and other literature. Based on the results of the research that has been done, it is concluded that the strategy adopted in dealing with the development of gold pawn products is in accordance with the theories and methods of developing innovations for Islamic banking products and in dealing with the problems of developing gold pawning products that occur, the Islamic bank KC Kabanajahe fulfills regular trends for programs by supplying customers, advancing the increase in gold pawning for products belonging to the Islamic bank KC Kabanajahe by persisting Mitigation of payments for payments that are met..